Pengembangan Media Pembelajaran Smart Book Netra (SBN) Inovasi Media Pembelajaran Pendidikan Karakter - Oviensy, Vegia; Kustati, Martin; Amelia, Reski; Afnita, Nora (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
The purpose of this study was to determine the level of validity of the Smart Book Netra (SBN) learning media prototype to improve student learning outcomes. In the current digital era, students are very active in using social media, especially Tiktok social media, which is 78% compared to other social media, even Tiktok social media users have increased by around 14.3 million per month. Seeing this problem, the researcher created a new innovation, Smart Book Netra (SBN), namely an innovation in character education learning media that can connect the virtual world with the real world at the same time. This media is also equipped with Braille letters that can be used by people with visual impairments. The type of research in writing this article is R&D using the Borg and Gall model. This study emphasizes the analysis of student needs. However, in this study, the researcher only reached the fifth stage, namely product revision. The data collection techniques in this study were through observation, questionnaires, literature studies, documentation and trials, then the analysis techniques used by the researcher were media expert validation, material expert validation analysis techniques and trial analysis techniques. The results of this study show that the Smart Book Netra (SBN) has a validity level of 92%.